HEMODYNAMIC PROFILE UNDER GENERAL ANESTHESIA IN CHILDREN DURING PLASTIC SURGERY (Herald of the National Children's Medical Center, 2022)
The aim: evaluating the effectiveness of anesthetic protection of a child during operations on the soft and hardpalate (palatoplasty, cheiloplasty) based on the study of hemodynamic parameters in conditions of combined methods ofgeneral anesthesia (OA) in combination with sevoHurane.Materials and Methods. A comparative analysis of the studies was carried out in 31 patients, aged from 9 months to3 years, who were operated on in a planned manner with pathology of the maxillofacial region (cleft palate, cleft lip). Correction of congenital clefts of the lip and palate is a signiKcant part of operations in plastic surgery departments. These patients undergo multi-stage surgical treatment. They often have comorbidities, anemia, and recurrent respiratory infections.Results. The results of the study indicate the advantages of using combined OA + sevoHurane: smooth intraoperativehemodynamic proKle, early recovery of spontaneous breathing with tracheal extubation on the operating table compared tothe control group.Conclusions: The combined OA technique (propofol + fentanyl) using the inhalation anesthetic sevoHurane provideseffective antinociceptive protection of the child during palatoplasty and cheiloplasty.
Keywords: central hemodynamics; adequacy of protection; inhalation anesthetic; hemodynamic proKle; palatoplasty